Assessing response, remission, and treatment resistance in patients with obsessive–compulsive disorder with and without tic disorders: results from a multicenter study. (16th December 2022) - Benatti, Beatrice; Girone, Nicolaja; Conti, Dario; Cafaro, Rita; Viganò, Caterina; Briguglio, Matteo; Marazziti, Donatella; Mucci, Federico; Gambini, Orsola; Demartini, Benedetta; Tundo, Antonio; Necci, Roberta; et al.
Abstract: Background: Highlighting the relationship between obsessive–compulsive disorder (OCD) and tic disorder (TD), two highly disabling, comorbid, and difficult-to-treat conditions, Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5) acknowledged a new "tic-related" specifier for OCD, ie, obsessive–compulsive tic-related disorder (OCTD). As patients with OCTD may frequently show poor treatment response, the aim of this multicenter study was to investigate rates and clinical correlates of response, remission, and treatment resistance in a large multicenter sample of OCD patients with versus without tics. Methods: A sample of 398 patients with a DSM-5 diagnosis of OCD with and without comorbid TD was assessed from 10 different psychiatric departments across Italy. For the purpose of the study, treatment response profiles in the whole sample were analyzed comparing the rates of response, remission, and treatment-resistance as well as related clinical features. Multivariate logistic regressions were performed to identify possible factors associated with treatment response. Results: The remission group was associated with later ages of onset of TD and OCD. Moreover, significantly higher rates of psychiatric comorbidities, TD, and lifetime suicidal ideation and attempts emerged in the treatment-resistant group, with larger degrees of perceived worsened quality of life and family involvement. Conclusions: Although remission was associated with later ages of OCD and TD onset, specific clinical factors, such as early onset and presence of psychiatric comorbidities and concomitant TD, predicted a worse treatment response with a significant impairment in quality of life for both patients and their caregivers, suggesting a worse profile of treatment response for patients with OCTD.